2012
DOI: 10.1371/journal.pone.0037323
|View full text |Cite
|
Sign up to set email alerts
|

Plant Food Delphinidin-3-Glucoside Significantly Inhibits Platelet Activation and Thrombosis: Novel Protective Roles against Cardiovascular Diseases

Abstract: Delphinidin-3-glucoside (Dp-3-g) is one of the predominant bioactive compounds of anthocyanins in many plant foods. Although several anthocyanin compounds have been reported to be protective against cardiovascular diseases (CVDs), the direct effect of anthocyanins on platelets, the key players in atherothrombosis, has not been studied. The roles of Dp-3-g in platelet function are completely unknown. The present study investigated the effects of Dp-3-g on platelet activation and several thrombosis models in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
75
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 58 publications
(92 reference statements)
0
75
1
1
Order By: Relevance
“…The potential anti-thrombotic mechanism of anthocyanins was investigated by Yang et al (2012) using delphinidin-3-glucoside which has an identical chemical structure to cyanidin-3-glucoside, except an additional OH-group in 5′-position of the B-ring (Kay, Mazza, & Holub, 2005). The authors concluded that delphinidin-3-glucoside exhibits its antithrombotic activity via the inhibition of the expression of P-selectin, CD63 and CD40L, a down-regulation of active integrin αIIbβ3, attenuation of fibrinogen binding, and reduction in phosphorylation of adenosine monophosphate-activated protein kinase.…”
Section: Parametersmentioning
confidence: 99%
“…The potential anti-thrombotic mechanism of anthocyanins was investigated by Yang et al (2012) using delphinidin-3-glucoside which has an identical chemical structure to cyanidin-3-glucoside, except an additional OH-group in 5′-position of the B-ring (Kay, Mazza, & Holub, 2005). The authors concluded that delphinidin-3-glucoside exhibits its antithrombotic activity via the inhibition of the expression of P-selectin, CD63 and CD40L, a down-regulation of active integrin αIIbβ3, attenuation of fibrinogen binding, and reduction in phosphorylation of adenosine monophosphate-activated protein kinase.…”
Section: Parametersmentioning
confidence: 99%
“…Our previous studies have shown that purified anthocyanin supplementation reduces the levels of inflammatory biological markers and improves serum lipids and endothelial function [3032]. We have also found that anthocyanins significantly inhibit platelet activation, thrombosis, platelet hyperactivity [33, 34] and platelet granule secretion of molecules such as CCL5, β-TG and soluble P-selectin (sP-selectin), both in vitro and in vivo [35]. However, the effects of purified anthocyanin supplementation on most other platelet chemokines in patients with hypercholesterolemia have not yet been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Intake of plants rich in phytochemicals is negatively associated with CVDs (12). Anthocyanins, one of the best-studied types of polyphenols, are abundant in various fruits and vegetables, such as black rice, grapes, berries, and red cabbage.…”
mentioning
confidence: 99%
“…However, it is difficult to explain the biological mechanism of anthocyanins because food extracts usually contain an enormous variety of bioactive compounds. Our previous studies have shown that the anthocyanin delphinidin-3-glucoside (Dp-3-g, another component of anthocyanins) can inhibit platelet activation and aggregation in vitro (11,12,14). We have also reported that capsules containing an anthocyanin mixture can inhibit platelet granule secretion in the plasma of patients with hypercholesterolaemia (11).…”
mentioning
confidence: 99%